ATMOSPHERIC EROSION AND RADIATION IMPULSE INDUCED BY IMPACTS - Shuvalov V.V.; Artemieva N.A. (My University, 2002)
Two effects of Chicxulub-scale impacts are considered: radiation impulse and impact-induced atmospheric erosion. Detailed numerical simulations show that radiation of the Chicxulub impact plume could be responsible for igniting wildfires over ∼3%-10% of the Earth's surface, close to the impact point. Atmospheric erosion is calculated based on detailed numerical modeling of all stages of the impact, including the flight through the atmosphere, cratering, and plume evolution. The mass of escaping air is found to be smaller than predicted by previous investigations. Preliminary results of three-dimensional numerical simulations show that oblique impacts are more effective from the viewpoint of atmospheric erosion.